Employees’ trust in supervisor and organizational citizenship behavior among bank employees - Mah, Suh Wei; Chua, Bee Seok; Tan, Cho Chiew (Unit Penyelidikan Psikologi dan Kesihatan Sosial UMS, 2018)
The purpose of this study was to investigate the influence of employees’ trust in their supervisor on their organizational citizenship behavior. This study also investigated the moderating effect of working experience in the relationship between employees’ trust and their organizational citizenship behavior. Data were collected from 163 employees working in local-owned and foreign-owned bank in Kota Kinabalu, Sabah. The Employees Trust Scale created by Chua et al. and Organizational Citizenship Behavior Scale by Smith et al. were used in this study. Result indicated that employees’ trust has positive and significant influence on their organizational citizenship behavior. Analysis on five subscales of employees’ trust indicated that the subscale of position status and relationship were the significant predictors of employee’s organizational citizenship behavior. Employee’s working experience had moderating effect in the relationship between employees’ trust and organizational citizenship behavior. However, the moderating effect only significant in the relationship between subscale of employer-employee relationship and organizational citizenship behavior among employees with less working experience. This study, it indicated that employees’ trust has an impact on organizational citizenship behavior (OCB) in banking industry. This study also found that employees’ working experience moderated the relationship between subscale of employer-employee relationship and organizational citizenship behavior.